Critical Review of Literature on Brand Equity and Customer Loyalty - Kegoro, Henry O; Justus, Munywoki (International Journal of Business, Economics and Management, 2020)
Brand equity is recognized as the driving force of customer loyalty in the competitive firms operating in the changing business environment. The culture of attracting and retaining customers is dependent on which organization can enhance the value of their products to conform and exceed customer needs. By extension, brand equity is regarded as a multi-dimensional facet that comprise of brand loyalty, brand awareness, brand association, perceived quality, brand association and proprietary assets. Theories and models which have been discussed extensively and inform the basis of arguments of this study include; brand equity theory, consumer utility theory, customer based brand equity model, service branding dominant logic model and brand evolution model. Despite conflicting ideologies and evolving nature of brand equity based on psychological aspects of consumers like attitudes and perceptions, it is noted that that there is a positive correlation between brand equity and customer loyalty. Based on the existing literature, it can be concluded that brand equity is the only strategic marketing initiative companies can enhance customer relations and sustainability. Therefore, it is recommended that companies should always strive to enhance their image in the mind of consumers by repositioning their brands in the market.